2019
DOI: 10.5430/ijfr.v11n1p43
|View full text |Cite
|
Sign up to set email alerts
|

Antecedent Variables and Consequences of Religiosity on Fraud

Abstract: This study aims to analyze the antecedent variables of religiosity (suitability of compensation, money ethics and internal control system) and the consequences on accounting fraud among regional officials. The study method used here was descriptive quantitative method with a correlation approach, the sampling used purposive sampling technique. Data collection in this study was conducted by distributing questionnaires to the officials of the Regional Work Units (SKPD) of Serang City and Regency. Data analysis u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Other studies, Boubraki et al (2011), proved that the concentration of ownership has affected negatively the firm value. Thus, it can be concluded that the concentration of ownership weakened the influences of dividends policy on the firm value (Taqi et al, 2020). Moreover, the research by Saona and Martin (2016) concluded that if the concentration of ownership increased, it might decrease the firm value.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies, Boubraki et al (2011), proved that the concentration of ownership has affected negatively the firm value. Thus, it can be concluded that the concentration of ownership weakened the influences of dividends policy on the firm value (Taqi et al, 2020). Moreover, the research by Saona and Martin (2016) concluded that if the concentration of ownership increased, it might decrease the firm value.…”
Section: Resultsmentioning
confidence: 99%